PEMAKNAAN PRODUK KONDOM SUTRA BAGI PEKERJA DAN PELANGGAN SEKS (Suatu Tinjauan Semiotika berdasarkan alur pemikiran Roland Barthes) - Daesy Ekayanthi (SEMIOTIKA: Jurnal Komunikasi, 2015)
Background this study discusses about Messages and Meaning in Social Semiotics, Semiotics of Roland Barthes an analysis of the messages in the Sutra Condoms Products have an impact on how the message recipient receives the message of Sutra Condom Products. In general, this thesis discusses about the connotations omessages on Sutra Condoms Products. For this study using the framework Semiotics of Roland Barthes as a theoretical framework, including about signified, signifier and denotation meaning on messages of Sutra Condoms Products. Beside that, the color of the Barker analysis is also used to assist the analysis in this study. This study uses Interpretive Paradigm. This paradigm is used departs from an attempt to find an explanation of the phenomenon of social events based on the interpretation and experience of those studied. Nature of the research is explorative aimed to explore and understand the significance of a reality that is stored in the mind or understanding of the subject / object. The method used is qualitative used was text analysis Semiotics of Roland Barthes with nature Single Case Single Analysis. Text has been created is certainly not independent of the context around it, so the interpretation is also studied customers and sex workers on text of Sutra Condom Product. Is this study it was found that: Obtained several texts that have been experienced in the context of a symbol to interpret the message on Sutra Condom Products is Sutra is a condom, Red is Condom of Sutra, Condom of Sutra is smooth and soft, Sutra condoms to prevent HIV / AIDS; Much of the information contained in packaging of Sutra Condom Products into the consumer's right to know as a user, actualy many are not interested in knowing more; Meaning connotation of more interest to consumers to use the products offered. Keyword: Messages and Meaning, Semiotics of Roland Barthes, Sutra Condoms Products, HIV/AIDS